(untitled) (Revista Internacional de Folkcomunicação, 2018)
In the late 1960s, Professor Luiz Beltrão shared his interest in investigating the TV news coverage. He understood how the electronic image was able to influence the watcher. Beltrão observed that TV’s technological and content revolution forced a behavior change of the press in both TV news language and publicity. He predicted, as a visionary, the emergence of companies of broadcasting similar CNN. Among the journalism competencies defined by Beltrão there are topicality and promotion. This article focuses on the idea of promotion, understood here in terms of the capacity of the TV spread news with social responsibility. Journalism; TV news; Topicality; Promotion.